The Planet Multiple. - Selcer, Perrin (Diplomatic History, 2025)
The article explores the complex relationship between internationalism, environmentalism, and Earth sciences, arguing that both unity and diversity must be acknowledged in understanding our planet's multiplicity. It critiques the notion of a singular Earth, emphasizing that different communities enact varied realities shaped by their unique worldviews and experiences. The author discusses how Earth system science (ESS) models, while presenting a unified planetary system, often obscure individual experiences and local histories, which can be better understood through the analysis of natural archives like sediment cores. Ultimately, the piece advocates for a nuanced approach that recognizes the interconnectedness of diverse narratives in addressing global environmental challenges.